Fermentation Optimization on Bacterial Cellulose Production by Acetobacter Xylinum 0416 - Esa, Faezah; Abd. Rahman, Norliza; Sahaid Kalil, Mohd; Masrinda Tasirin, Siti (International Journal of Engineering and Technology, 2019)
Bacterial cellulose (BC) has received extensive attention in various field due to of its high purity, mechanical strength, crystallinity and biodegradability. Determination of optimum fermentation condition for the improvement of cellulose production is essential especially in industrial scale. The production of bacterial cellulose by A.xylinum 0416 was fermented in matured coconut water medium and the suitable culture conditions were predicted statistically via Central Composite Design of Response Surface Methodology. Effect of varying temperature, fermentation period, initial pH, inoculum size and parameters interaction were studied in five-levels Design of Experimental approach. Temperature, inoculum size and fermentation period had significant effects on the cellulose production. By aiming to minimize the temperature and fermentation period for maximum cellulose production, the optimized parameters predicted for cellulose production of 1.12829 g dry weight were temperature: 27˚C, fermentation period: 5 days, initial pH: pH 8 and inoculum size: 15% with high desirability of 78.2%.